149k views
2 votes
Solve the equation. Simplify your answer if possible.
((x+2)/5)+((x+1)/3)=((x-3)/10)-2​

1 Answer

1 vote

Answer:

The solved given equation


((x+2)/(5))+((x+1)/(3))=((x-3)/(10))-2 is x=-7

Explanation:

Given equation is
((x+2)/(5))+((x+1)/(3))=((x-3)/(10))-2

To solve the given equation as below :


((x+2)/(5))+((x+1)/(3))=((x-3)/(10))-2 ( by using the distributive property )


(3x+6+5x+5)/(15)=(x-3-20)/(10) ( adding the like terms )


(8x+11)/(15)=(x-23)/(10)

Multiply into (10(15) on both sides we get


(8x+11)/(15)* (10)(15)=(x-23)/(10)* (10)(15)


(8x+11)* (10)=(x-23)* (15) ( by using the distributive property )


80x+110-15x+345=0 ( adding the like terms )


65x+455=0


65x=-455


x=-(455)/(65)

Therefore x=-7

Therefore the solved given equation is x=-7

User Tuhin
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.